Entry and exit in severe recessions: lessons from the 2008–2013 Portuguese economic crisis - Carreira, Carlos (2016)
Under cleansing, productivity-enhancing reallocation is expected to be accelerated in recessions. In this paper we contribute to the analysis of one component of the national systems of entrepreneurship (namely capital market frictions) by showing that in the extreme scenario of deep recession efficiency in resource reallocation can actually be reduced. Using data from the pronounced Portuguese economic crisis, we do find a spike in firm exit in 2008–2012 vis-à-vis the 2004–2007 pre-crisis period, and a substantial increase in job destruction as well. But we did not find any strong evidence that job reallocation is countercyclical, while a non-negligible fraction of high-productivity firms actually shut down. In turn, our selected proxies for strictness in credit markets reveal that in deep recessions they are seemingly associated with increased firm exit and lower employment creation. Taken in round, our results show that credit market stringency in conjunction with an unfavourable economic cycle is likely to generate a long-lasting destructive process.